LARANGAN MENYEMBUNYIKAN ILMU DALAM PERSPEKTIF OPEN ACCES DAN KEBEBASAN INFORMASI - Yusbayani Yusbayani; Nur Iman Saal; Tasbih Tasbih; Subehan Khalik (Universitas Muhammadiyah Bandung, 2026)
Advances in digital technology and the open-access movement have transformed the global distribution of knowledge, including in Islamic studies. However, information openness in the digital age still faces various challenges, such as restricted access to knowledge, knowledge monopolies, the spread of unverified information, and a weak ethical foundation in the dissemination of knowledge. On the other hand, the hadith of the Prophet Muhammad (peace be upon him) regarding the prohibition against concealing knowledge indicates a moral responsibility to convey knowledge for the benefit of the community. This study aims to interpret the hadith on the prohibition against concealing knowledge from the perspective of open access and freedom of information, as well as to analyze its relevance to the practice of knowledge dissemination in the digital age. The study employs a qualitative method using a library research approach. Data were obtained from the major hadith collections (Kutubus Sittah), hadith commentaries, literature on open access and freedom of information, as well as relevant scholarly articles. Data analysis was conducted using hadith authentication techniques, hadith commentary, thematic analysis, and comparative analysis. The results of the study indicate that hadiths regarding the prohibition of concealing knowledge affirm that knowledge is a social trust that must be disseminated responsibly. This principle is substantively aligned with the concept of open access, particularly in terms of open access to knowledge, equitable distribution of knowledge, and public benefit. However, Islam . This study employed a qualitative method using a library research approach. Data were obtained from the major hadith collections (Kutubus Sittah), hadith commentaries, literature on open access and freedom of information, as well as relevant scholarly articles. Data analysis was conducted using hadith takhrij techniques, hadith commentaries, thematic analysis, and comparative analysis. The results indicate that the hadiths regarding the prohibition against concealing knowledge affirm that knowledge is a social trust that must be disseminated responsibly. This principle aligns substantively with the concept of open access, particularly regarding open access to knowledge, equitable distribution of knowledge, and public benefit. However, Islam also emphasizes ethical boundaries in the form of information verification, the competence of the disseminator, and a focus on the public good. These findings indicate that Islam not only supports the openness of knowledge but also offers an ethical framework for the distribution of knowledge that is relevant to the development of information systems and scientific publications in the digital age.